Bronchial Dieulafoy's Disease in Children: A Case Report and Review of Literature - Yi-Ting Yeh; Yi-Ting Yeh; Madhavan Ramaswamy; Jinnie Shin; Denise McIntyre; Neil McIntosh; Jean-Nicolas Racicot; Samantha Chippington; Samuel Stuart; Nagarajan Muthialu (Frontiers Media S.A., 2020)
Dieulafoy's disease is a rare vascular lesion characterized by presence of large aberrant arteries within the submucosa of gastrointestinal tract or respiratory tract with a potential to cause life-threatening hemorrhage. Treatment includes bronchoscopy ablation, angiographic embolization or surgery. We report management of 7-year old girl with Dieulafoy's disease in the airway who presented with recurrent hemoptysis. Bronchial angiography revealed multiple feeding vessels to the lesion. Considering the potential risk of recurrence with embolization, sleeve resection of bronchus offered complete resolution. This case demonstrates the usefulness of bronchial angiography as part of multi-faceted approach before surgery in the management of Dieulafoy's disease.